Application of continuum decohesive finite element to progressive failure analysis of composite materials. (15th March 2019) - Lin, Shiyao; Nguyen, Nhung; Waas, Anthony M.
Abstract: The continuum decohesive finite element (CDFE) is a novel finite element technique combining continuum and cohesive crack modeling seamlessly. In CDFE, the transition from a continuum to non-continuum is modeled physically by introducing pairs of dummy nodes to account for the crack separations. A static condensation algorithm is applied to solve for and preserve the separations. In this paper, CDFE has firstly been applied to the modeling of transverse crack growth in a representative volume element (RVE) of composite materials. Microscopic cracks initiate separately and coalesce into a macroscopic transverse crack. In this case, mode I cracking is dominant and the maximum principal stress criterion is used for crack angles. The second problem set is the delamination toughness tests, including a double cantilever beam (DCB) test, an end notched flexure (ENF) test and mixed mode bending (MMB) tests of three mixed mode ratios. In these cases, the crack plane is well-defined and mode mixity is encountered. For better numerical stability, the CDFE inner-element discretization scheme is modified and a novel mixed mode cohesive formulation is implemented. Through analyses, the capability of CDFE to deal with general progressive failure problems of composite materials is shown.